Effect of Organizational Culture, Work Engagement, and Communication Skills on Employee Performance in PT Dimas Pratama Indah - Anisa Rahma Dini; Septa Diana Nabella; Nurmayunita Nurmayunita (International Journal of Economics, Business and Innovation Research, 2024)
The company's success depends on employee performance. This research was conducted to determine the influence of organizational culture, work engagement and communication skills on employee performance at PT Dimas Pratama Indah in Batam City. This research used a causality design with a population of 65 people. The sampling technique was saturated sampling, totaling 65 people. The data analysis method used is the multiple linear regression analysis method using the SPSS version 25 program. The results of the test show that organizational culture and communication skills have no partial effect on employee performance, while work engagement have a partial effect on employee performance. Organizational culture, work engagement and communication skills simultaneously have a positive and significant effect on employee performance.